Modulation of Tomato Response to Rhizoctonia solani by Trichoderma harzianum and Its Secondary Metabolite Harzianic Acid - Manganiello, Gelsomina; Sacco, Adriana; Ercolano, Maria R.; Vinale, Francesco; Lanzuise, Stefania; Pascale, Alberto; Napolitano, Mauro; Lombardi, Nadia; Lorito, Matteo; Woo, Sheridan L. (Frontiers in Microbiology, 2018)
The present study investigated the transcriptomic and metabolomic changes elicited in tomato plants (Solanum lycopersicum cv. Micro-Tom) following treatments with the biocontrol agent T. harzianum strain M10 or its secondary metabolite harzianic acid (HA), in the presence or absence of the soil-borne pathogen Rhizoctonia solani. Transcriptomic analysis allowed the identification of differentially expressed genes (DEGs) that play a pivotal role in plant growth, development and resistance to biotic stress. Overall, the results support the ability of T. harzianum M10 to activate defense responses in infected tomato plants. We observed an induction of hormone-mediated signaling, as shown by the up-regulation of genes involved in the ethylene and jasmonate (ET/JA) biosynthesis. Further, the protective action of T. harzianum on the host was revealed by the over-expression of genes able to detoxify cells from reactive oxygen species (ROS). Moreover, the over-expression of genes involved in glycolysis, tricarboxylic acid cycle (TCA) and photosynthesis help to understand how this strain promotes plant growth and development. On the other hand, HA treatment also stimulated tomato response to the pathogen by inducing the expression of several genes involved in different defense mechanisms (including protease inhibitors, resistance proteins like CC-NBS-LRR) and activating ET/JA- and salicylic acid (SA)-mediated signaling pathways. The accumulation of steroidal glycoalkaloids caused by either T. harzianum or purified HA, as determined by metabolomic analysis, confirmed the complexity of the plant response to beneficial microbes in terms of secondary metabolism involved in defense mechanisms against pathogens.